Non-Pharmacological Treatment Options for Patients with Fibromyalgia - Rahman, Md Shahidur (Journal of Enam Medical College, 2018)
Fibromyalgia is a generalized chronic pain syndrome characterized by widespread pain and tenderness to palpation at multiple anatomically defined soft tissues and associated with depression, anxiety, insomnia, cognitive dysfunction, chronic fatigue, and autonomic dysfunction. In 2010, American College of Rheumatology modified classification criteria defined in 1990. This is one of the most common musculoskeletal complaints in physician’s chambers. For lack of specific pharmacological treatment options, non-pharmacological treatment modalities are found to have some immediate efficacy and a variable efficacy in the long term. We searched literatures and reviewed randomized controlled trials for possible predictors of outcome in fibromyalgia. The effects of non-pharmacological interventions are limited and positive outcomes largely disappear in the long term. However, within the various populations with fibromyalgia, treatment outcomes showed considerable individual variations. Subgroups of patients with high levels of psychological distress may benefit from non-pharmacological interventions. Some of the relevant published articles demonstrated the beneficial effects of non-pharmacological treatment options, specially exercise, cognitive behavioral therapy and alternative and complementary medicine, in the context of non-availability of specific pharmacotherapy. J Enam Med Col 2018; 8(3): 165-169